Development of a multivalent adjuvanted inactivated vaccine against variant arthrotropic avian reoviruses - Ayalew, Lisanework E.; Popowich, Shelly; Chow-Lockerbie, Betty; Gautam, Hemlata; Subhasinghe, Iresha; Ahmed, Khawaja Ashfaque; Tikoo, Suresh K.; Ojkic, Davor; Gomis, Susantha (Frontiers in Veterinary Science, 2023)
Variant avian reoviruses (ARVs) are economically important emerging pathogens of poultry, which mainly affect young broiler chickens and cause significant production losses. Currently, there are no effective commercial vaccines available for control and prevention of emerging variant ARVs.In this study, monovalent inactivated adjuvated (20% Emulsigen D) broiler breeder vaccines containing antigens from ARV genotype cluster (C) group -2, -4, -5, or -6, and a multivalent vaccine containing antigens from all the four indicated genotypic cluster groups were developed and evaluated for their efficacy in protecting broiler progenies against homologous or heterologous ARV challenge. The use of monovalent or multivalent inactivated vaccines in a prime-boost immunization strategy induced the production of ARV specific antibodies in broiler breeders. The maternal antobodies were effectively transferred to broiler progenies. Broiler progenies obtained from immunized breeders demonstrated milder clinical symptoms and reduced gross and histopathological lesions after homologous ARV challenge. More severe gross and histological lesions were observed in challenged progenies from unvaccinated broiler breeders. However, cross protection was not observed when either of the monovalent-vaccine groups were challenged with a heterologous virus. In addition, the progenies from the unvaccinated ARV challenged control or heterologous ARV challenged vaccinated groups had significantly reduced body weight gain (p<0.01) than the unchallenged-control, challenged-multivalent, or homologous ARV-challenged monovalent vaccine groups. However, homologous ARV challenged progenies in the multivalent or monovalent vaccine groups had similar body weight gain as the control unchallenged group with significantly reduced viral load (p<0.01) in the gastrocnemius tendon tissue. This study indicates that broad-spectrum protection of broiler progenies from variant ARV infections is feasible through the development of multivalent vaccines after proper characterization, selection and incorporation of multiple antigens based on circulating ARV genotypes in targeted regions.